USER ACCEPTANCE OF MOBILE-JKN: INSIGHTS FROM THE TECHNOLOGY ACCEPTANCE MODEL - Damanik, Ferina Septiani; Widayanti, Anna Wahyuni; Wiedyaningsih, Chairun (Universitas Airlangga, 2024)
Background: Technological advancements in healthcare have driven BPJS Kesehatan Indonesia to develop the Mobile JKN application to enhance accessibility, efficiency, and quality of services. Despite its potential benefits, the implementation of this application faces various challenges, such as application errors, differing levels of digital literacy, and data security issues, necessitating an evaluation of its adoption and acceptance. Aims: To analyse the public acceptance of Mobile JKN based on the Technology Acceptance Model (TAM) variable while also exploring user experiences towards the application. Methods: A descriptive-analytical approach with a cross-sectional design. Data were collected through a questionnaire developed based on the TAM model, involving 406 respondents across Indonesia. Data analysis was performed using a regression linear test with SPSS after all basic assumptions were met. Results: Perceived Ease of Use, Perceived Usefulness, and Attitude Toward Use individually and simultaneously impact Actual System Use (Sig. 0.000; R-Square 0.827). Respondents generally answered “Agree” to all TAM indicators, with mean scores of 4.20 for Perceived Usefulness, 4.16 for Perceived Ease of Use, 4.25 for Attitude Toward Use, and 4.33 for Actual System Use. Most users accessed the app through self-access (48%), frequently used features were membership information (28%), and encountered issues such as application errors (25%). Conclusion: The app was deemed relevant, accurate, easy to use, and beneficial. To enhance public acceptance, BPJS Kesehatan should focus on developing a user-friendly Mobile JKN app by incorporating key TAM factors, optimizing popular features, improving technical stability, and regularly addressing user feedback to ensure effective health administration and service delivery. Keywords: Adoption, Application, BPJS Kesehatan, Mobile JKN, TAM